Speeches that Changed the World - Compiled by Cathy Lowne (London Bounty Books, 2005)
The speeches in this book are divided into the following chapters: Ancient History, Love, Religion, Science, Patriotism, Philosophy, Humanity & Liberty, Sport, Plitics, & War. Many of them have inspired people to act, some have changed the way people think or look at the world. Others have changed the course of events across the globe - sometimes for the better, at other times with devastating results. All have chronicled our history.
Include Acknowledgement and Index.
Over 100 of the more influential speeches ever made.
Keywords: Speeches -- World history -- Addresses